The Influence of Oil Price Fluctuations on Stock Market of Developing Economies: A Focus on Nigeria - Nwude, Chuke; Eluyela, Damilola Felix; Agbo, Elias Igwebuike; Iyoha, Francis O (International Journal of Energy Economics and Policy, 2021)
The inconclusiveness of findings from various studies on Nigeria on the effect of crude oil price fluctuation on the stock market has led to an argument in literature, thus necessitating further exploration of the subject. This study examines the effect of variations in the price of crude oil on selected stock market performance variables in Nigeria using monthly frequency data covering January 1997 to December 2016. Variance decomposition, impulse response analysis, and VAR estimations were employed for the study. The results reveal that oil price variations are slowly transmitted in some stock market performance variables. The findings indicate that the effect of crude oil price fluctuations in the Nigerian stock market is greatly minimized and does not sufficiently account for market activities. Keywords: Emerging Economy, Nigeria, Oil Price Shocks, Stock Market, VAR. JEL Classifications: C25, Q47, F4 DOI: https://doi.org/10.32479/ijeep.10140